STATUS AND PROSPECTS OF INCREASING COOPERATION OF THE TERRITORIAL COMMUNITIES OF THE POLTAVA REGION - DOROFYEYEV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study revealed the relevance of the issue of cooperation between territorial communities in Ukraine. The purpose of the study is to characterize the current state of development of cooperation between territorial communities in the Poltava region of Ukraine, to identify weak points and problematic aspects, and to substantiate directions for the activation of intermunicipal cooperation. The number of agreements and the number of cooperation partners of territorial communities within one cooperation agreement were analyzed. The activity of territorial communities regarding the conclusion of cooperation agreements by functional directions (spheres) of cooperation is characterized. Information on the number of cooperation agreements of territorial communities of the region in the spatial aspect is presented. The duration of inter-municipal cooperation of communities has been determined. A description of the activities of territorial communities in relation to participation in the regional project competition, in particular in the part of using the instrument of inter-municipal cooperation, is given. The structure of inter-municipal cooperation of territorial communities of Poltava region by spheres of cooperation is given. The applied value of the research results is that the problem areas and obstacles of inter-municipal cooperation of communities in the region have been identified, which is a strong informational and analytical basis for the development of a more effective regional policy of activation and effectiveness of cooperation of territorial communities. The scientific novelty of the research results is that the methodology for analyzing the scope and quality of inter-municipal cooperation of territorial communities of the region has been further developed.